2007
DOI: 10.1016/j.vaccine.2007.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal immunization with synthetic peptides corresponding to the E6 and E7 oncoproteins of human papillomavirus type 16 induces systemic and mucosal cellular immune responses and tumor protection

Abstract: The E6 and E7 oncoproteins of the high-risk HPV type16 represent ideal targets for HPV vaccine development, they being consistently expressed in cervical cancer lesions. Since HPV-16 is primarily transmitted through genital mucosal route, mucosal immune responses constitute an essential feature for vaccination strategies against HPV-associated lesions. We present here evidence showing that mucosal immunization of mice by the intranasal route with a mixture of peptides E7 44-62 and E6 43-57 from the E7 and E6 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 39 publications
1
34
0
1
Order By: Relevance
“…E7 44-57 contains a CD4 + T helper cell epitope (E7 [48][49][50][51][52][53][54] , DRAHYNI) and a CD8 + T cell epitope (E7 49-57 , RAHYNIVTF), 11,12 similarly E6 43-57 also includes both CD4 + and CD8 + epitopes. 13 Recently, we showed that E7 [44][45][46][47][48][49][50][51][52][53][54][55][56][57] conjugated to a polymeric delivery system was able to eradicate E7-expressing tumor cells in immunized mice. 11,12,14 tert-Butyl acrylate polymer was chosen as a delivery platform for the vaccine because of its safety profile 15 and ability to serve as a self-adjuvanting moiety to induce both strong humoral and cellular immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…E7 44-57 contains a CD4 + T helper cell epitope (E7 [48][49][50][51][52][53][54] , DRAHYNI) and a CD8 + T cell epitope (E7 49-57 , RAHYNIVTF), 11,12 similarly E6 43-57 also includes both CD4 + and CD8 + epitopes. 13 Recently, we showed that E7 [44][45][46][47][48][49][50][51][52][53][54][55][56][57] conjugated to a polymeric delivery system was able to eradicate E7-expressing tumor cells in immunized mice. 11,12,14 tert-Butyl acrylate polymer was chosen as a delivery platform for the vaccine because of its safety profile 15 and ability to serve as a self-adjuvanting moiety to induce both strong humoral and cellular immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…We have formulated these peptides and the adjuvant alpha-galactosylceramide (αGalCer) into an intranasal (i.n.) vaccine, which evokes both mucosal and systemic E6/E7 T-cell responses (12). In the syngeneic C57BL/6 HPV E6/ E7-positive TC-1 tumor model, this vaccine alone significantly delayed the growth of 6-d established tumors and extended survival by more than 20 d. Addition of 4-1BB agonist antibodies, but not blockade of either CTLA-4 or PD-1, converted this therapeutic E6/E7 peptide vaccine into a curative therapy capable of inducing tumor regression, and complete elimination of the majority of s.c. implanted and all vaginally implanted TC-1 tumors.…”
mentioning
confidence: 99%
“…Three adult rhesus macaques were immunized by oral priming with the enteric-coated capsules containing the Ad-gag and Ad-env-peptide constructs, and induction of antigen-specific humoral and cellular immune responses were observed. The peptide-specific cellular responses were boosted by intranasal delivery of the peptide-cocktail using a mutant cholera toxin that was effective as a mucosal adjuvant in our earlier murine studies [25,26]. These results in a non-human primate model provide proof of principle for a prime-boost HIV vaccination strategy employing Ad vectored antigens for priming and peptides/proteins in combination with the CT2* adjuvant for boosting in order to generate mucosal and systemic protective immunity.…”
Section: Introductionmentioning
confidence: 76%
“…At weeks 28 and 32, the macaques received intranasal immunization 100 μg each of six HIV-1 envelope peptides mixed with the mucosal adjuvant CT2* [25,26] While all three monkeys had positive proliferation responses after priming, boosting with the peptides mediated only slight increase in these responses against env when PBMCs were stimulated with the same peptides in vitro (Fig. 4A).…”
Section: Intranasal Boosting With Synthetic Peptides Adjuvanted With mentioning
confidence: 99%